Successful salvage of a severe COVID-19 patient previously with lung cancer and radiation pneumonitis by mesenchymal stem cells: a case report and literature review - Huang, Xiaohua; Tan, Xin; Xie, Xiuwen; Jiang, Tingshu; Xiao, Yang; Liu, Zenghui (Frontiers in Immunology, 2024)
During the COVID-19 pandemic, elderly patients with underlying condition, such as tumors, had poor prognoses after progressing to severe pneumonia and often had poor response to standard treatment. Mesenchymal stem cells (MSCs) may be a promising treatment for patients with severe pneumonia, but MSCs are rarely used for patients with carcinoma. Here, we reported a 67-year-old female patient with lung adenocarcinoma who underwent osimertinib and radiotherapy and suffered from radiation pneumonitis. Unfortunately, she contracted COVID-19 and that rapidly progressed to severe pneumonia. She responded poorly to frontline treatment and was in danger. Subsequently, she received a salvage treatment with four doses of MSCs, and her symptoms surprisingly improved quickly. After a lung CT scan that presented with a significantly improved infection, she was discharged eventually. Her primary disease was stable after 6 months of follow-up, and no tumor recurrence or progression was observed. MSCs may be an effective treatment for hyperactive inflammation due to their ability related to immunomodulation and tissue repair. Our case suggests a potential value of MSCs for severe pneumonia that is unresponsive to conventional therapy after a COVID-19 infection. However, unless the situation is urgent, it needs to be considered with caution for patients with tumors. The safety in tumor patients still needs to be observed.